2015
DOI: 10.1007/s12149-015-0968-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of 64CuCl2 PET/CT in staging of prostate cancer

Abstract: The preliminary results of this study show a high uptake of (64)CuCl2 in PC and involved regional lymph nodes indicating to a great potential of (64)CuCl2 PET/CT for primary staging of patients with prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 15 publications
4
61
3
Order By: Relevance
“…However, what is clear is that the extrapolation of animal (mice and rats) data to humans’ incorrectly identify the critical organ, and underestimate radiation absorbed doses for [ 64 Cu]CuCl 2 . Radiation dosimetry estimates of [ 64 Cu]CuCl 2 using biodistribution data from patients with prostate cancer [8] are also underestimated compared to dose estimates based on biodistribution data obtained from healthy volunteers. The difference of radiation-absorbed doses to specific organs and effective doses presented in Table 3 could be explained in part by the altered biodistribution of [ 64 Cu]CuCl 2 in prostate cancer patients, as it has been demonstrated that the biodistribution of 64 Cu in tumor-bearing animals is altered as compared with that of the corresponding control animals [17, 18], but given the subjectivity of the process of curve fitting, volume drawing, and assumptions in the dose calculations, the differences between our results and those previously reported by Capasso et al are most likely not just due to altered biodistribution but due to the analysis technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, what is clear is that the extrapolation of animal (mice and rats) data to humans’ incorrectly identify the critical organ, and underestimate radiation absorbed doses for [ 64 Cu]CuCl 2 . Radiation dosimetry estimates of [ 64 Cu]CuCl 2 using biodistribution data from patients with prostate cancer [8] are also underestimated compared to dose estimates based on biodistribution data obtained from healthy volunteers. The difference of radiation-absorbed doses to specific organs and effective doses presented in Table 3 could be explained in part by the altered biodistribution of [ 64 Cu]CuCl 2 in prostate cancer patients, as it has been demonstrated that the biodistribution of 64 Cu in tumor-bearing animals is altered as compared with that of the corresponding control animals [17, 18], but given the subjectivity of the process of curve fitting, volume drawing, and assumptions in the dose calculations, the differences between our results and those previously reported by Capasso et al are most likely not just due to altered biodistribution but due to the analysis technique.…”
Section: Discussionmentioning
confidence: 99%
“…Future clinical applications of [ 64 Cu]CuCl 2 will require accurate dosimetric data, especially for therapeutic procedures; however, only limited human biodistribution data and organ dosimetry are currently available for this radionuclide in the chemical form of copper chloride. Capasso et al obtained human biodistribution data from patients with prostate cancer and estimated radiation doses, but the main purpose of Capasso’s research was not to perform the dosimetry but to investigate the role of [ 64 Cu]CuCl 2 PET/CT in staging of prostate cancer [8]. The dosimetric calculations were performed with limited data points, which limit the confidence in the data curve-fitting for determining the time-integrated activity coefficients in source organs.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the findings of age-dependent changes of 64 Cu accumulation in Atp7b −/− knockout mice support further study of age-dependent changes of cerebral copper fluxes in WD patients using [ 64 Cu]CuCl 2 -PET/CT imaging. Radiation dosimetry of [ 64 Cu]CuCl 2 estimated from preclinical biodistribution and radiation dosimetry studies in rodents [7, 8, 32] and clinical use of [ 64 Cu]CuCl 2 as a radiopharmaceutical for diagnostic imaging of prostate cancer in human [33] support safe use of [ 64 Cu]CuCl 2 as a tracer for evaluation of cerebral copper metabolism imbalance in WD patients. In view of a tiny amount of copper ions (< 0.04 ng/μCi of 64 CuCl 2 ) in a tracer dose of [ 64 Cu]CuCl 2 , there is little concern of copper toxicity on neurons when a tracer dose of [ 64 Cu]CuCl 2 is administered for PET/CT imaging in human.…”
Section: Discussionmentioning
confidence: 99%
“…Age-dependent changes of brain copper fluxes in Atp7b −/− knockout WD mice was demonstrated by a longitudinal PET study using orally administered 64 CuCl 2 as a radiotracer [64]. Moreover, 64 CuCl 2 was successfully used as a radiotracer for diagnostic imaging of prostate cancer [65] and brain tumors [66] in humans with PET, based on previous use of 64 CuCl 2 as a tracer for localization of human prostate cancer xenograft tumors in rodents [67]. The findings from these studies support use of 64 CuCl 2 as a radiotracer for quantitative analysis of age-dependent changes of copper fluxes in brain aging and pathophysiology of AD with PET [6870].…”
Section: Coppermentioning
confidence: 99%